A Descriptive Study on Nesting Patterns of Raptors; White Backed Vulture (Gyps africanus) and African Fish Eagle (Haliaeetus vocifer), in Lochinvar National Park on the Kafue Flats, Zambia - Chansa Chomba; Eneya M’Simuko (Challenging Issues on Environment and Earth Science Vol. 5, 2021)
This study assessed the nesting patterns of raptors, White backed vulture (Gyps africanus) and African fish eagle (Haliaeetus vocifer) in Lochinvar National Park, Zambia. The main objective of the study was to determine whether tree species, height, girth size, and habitat influenced raptor’s nest placement within Lochinvar National Park. Two species were selected as ecological indicator for all the raptors. Habitat types and tree species were identified and measurements of tree species with nests taken. It was found that the minimum height of nest placement was 10 meters above ground and Acacia woodland was found to be the most preferred habitat for nest placement. Raptors avoided human disturbance such as roads by placing their nests at least 100 meters away from human disturbance and from the National Park boundary inwards or abandoning if human encroachment comes close to the nest. Opening of new roads, construction of new buildings as well as increase in human activities in such habitats may lead to raptors abandoning their nests. New infrastructure in the National Park should avoid areas with high density of raptor nests as they are known to return to the same nest to lay eggs. More research is required to assess nesting materials used, and to determine whether raptors can swap nets or return to the abandoned nests when human disturbance ceases.